Reducing the carbon footprint of diets across socio-demographic groups in Finland: a mathematical optimisation study - Irz, Xavier; Tapanainen, Heli; Saarinen, Merja; Salminen, Jani; Sares-Jäske, Laura; Valsta, Liisa M (Cambridge University Press, 2024)
Objectives: To characterise nutritionally adequate, climate-friendly diets that are culturally acceptable across socio-demographic groups. To identify potential equity issues linked to more climate-friendly and nutritionally adequate dietary changes. Design: An optimisation model minimises distance from observed diets subject to nutritional, greenhouse gas emissions (GHGE) and food-habit constraints. It is calibrated to socio-demographic groups differentiated by sex, education and income levels using dietary intake data. The environmental coefficients are derived from life cycle analysis and an environmentally extended input–output model. Setting: Finland. Participants: Adult population. Results: Across all population groups, we find large synergies between improvements in nutritional adequacy and reductions in GHGE, set at one-third or half of the current level. Those reductions result mainly from the substitution of meat with cereals, potatoes and roots and the intra-category substitution of foods, such as beef with poultry in the meat category. The simulated more climate-friendly diets are thus flexitarian. Moving towards reduced-impact diets would not create major inadequacies related to protein and fatty acid intakes, but Fe could be an issue for pre-menopausal females. The initial socio-economic gradient in the GHGE of diets is small, and the patterns of adjustments to more climate-friendly diets are similar across socio-demographic groups. Conclusions: A one-third reduction in GHGE of diets is achievable through moderate behavioural adjustments, but achieving larger reductions may be difficult. The required changes are similar across socio-demographic groups and do not raise equity issues. A population-wide policy to promote behavioural change for diet sustainability would be appropriate.
Keywords: diet; food consumption; optimisation; sustainability; climate change; environmental impact; just transition